ChemInform Abstract: Enantioselective Synthesis of Tertiary α‐Chloro Esters by Non‐covalent Catalysis. Issue 38 (3rd September 2015) - Liu, Richard Y.; Wasa, Masayuki; Jacobsen, Eric N.
Abstract The enantioselective α‐chlorination of silyl ketene acetals with NCS is achieved in the presence of the chiral squaramide catalyst.